Oral leukoplakia - an investigation of its microbiome and of the association of clinical and microbial features with the degree of dysplasia - Galvin, Sheila (School of Dental Sciences, 2024)
Background: With growing evidence of a shift in the oral microbiome associated with oral squamous cell carcinoma, it was hypothesised that the microbiome of oral leukoplakia (OLK), the most common of the 11 recognised oral potentially malignant disorders in the Western world, also differed from that of normal mucosa. Aims: The aims of this study were to establish (1) if OLK was associated with changes in the oral microbiome and whether these changes differed with different degrees of dysplasia, (2) which clinical and patient factors were associated with the degree of dysplasia of OLK (3) how other factors such as smoking affected the oral mucosal microbiome and (4) if changes in the microbiome could be used to predict whether an OLK was low risk (no or mild dysplasia [LROLK]) or high risk (moderate or severe dysplasia [HROLK]). Methods: Following ethical approval, swabs were taken from histologically proven OLKs and contralateral normal sites (CLN) in patients who met the inclusion criteria. Healthy controls (HC) were also sampled at various mucosal sites. After DNA extraction, the V1-V3 region of the 16S rRNA gene was sequenced. RStudio was used for statistical analysis. Results: Prior to DNA extraction, analysis of 225 OLKs from 186 patients found that OLKs on the dorsum/lateral tongue had a 38.6 times, and on the floor of mouth/ventral tongue a 70.4 times, increased relative risk of being severely dysplastic compared with OLKs on the buccal mucosa. Non-homogeneity was also significantly associated with severe dysplasia (p=0.0005). Investigation of the microbial communities of healthy mucosal surfaces (n=322, 202 CLN and 120 HC) found that the most significant influences on the microbiome of clinically normal mucosa were smoking and oral site, smoking being associated with a shift to a more periodontal pathogen-heavy microbiome. Site specificity was also identified. Comparison of the microbial communities of 216 OLK and 202 CLN sites found that OLK, after adjusting for multiple variables, was consistently associated with increased abundance of five taxa: Bergeyella sp. HMT322, Streptococcus australis infantis clade 431, Gemella morbillorum, Leptotrichia sp. HMT215 and Leptotrichia sp. HMT392. Separate analysis found that the microbial communities of LROLK [n=91] and HROLK [n=125] exhibited significant differences. After adjusting for multiple variables, LROLKs were consistently associated with significantly increased abundances of Gemella morbillorum and Mogibacterium diversum, while HROLKs were associated with significantly increased abundances of Bergeyella sp. HMT322, Streptococcus australis infantis clade 431 and Leptotrichia sp. HMT215. Finally, predictive modelling using the top 50 microbial features from a preliminary modelling analysis could differentiate HROLK from LROLK with a sensitivity of 85.5% and specificity of 76.5%, while a combined model using both clinical/patient and microbial features could predict LROLK or HROLK with a sensitivity of 87.4% and specificity of 76.5%. Conclusion: The microbiome of OLK differs significantly from that of healthy mucosa. OLKs with different degrees of dysplasia have altered microbial communities which could, in future, be used to predict if an OLK is low or high-risk. Aside from presence of OLK, smoking and oral site were the most significant influences on the oral mucosal microbiome. Finally, OLK location on the tongue or floor of mouth and non-homogeneity were associated with severe dysplasia.
Keywords: Oral leukoplakia, oral microbiome, oral epithelial dysplasia, oral squamous cell carcinoma